Distinctive features of spatial planning nearby estuaries – An exploratory analysis of water-related rules in municipal master plans in Portugal. (5th July 2021) - Rodrigues, Carla; Fidélis, Teresa
Abstract: Land-use types and related intensities are often associated with pressures and disturbances on estuarine environmental values and ecosystem services provided by water. Although with varied legal frameworks across countries, broadly, spatial planning has been expected to contribute to the protection of environmentally sensitive areas, such as estuaries. Among the various planning tools are the plan's land-use control rules. This article studies the incorporation of water-related terms in the regulations of municipal master plans to assess if land-use rules established on estuarine areas are significantly different from others, such as in upstream areas. It does so by developing a content analysis of a set of plans' regulations located in estuarine and upstream areas of two river basins of Mainland Portugal. The results show greater incorporation of water-related terms in plans' regulations located in estuarine areas. Moreover, they show a greater diversity of water-related topics, types, and focus of rules on estuarine areas, whereas on upstream areas the regulatory approaches look poorer. Although the incorporation of water-related terms is globally higher in younger plans, and to a certain extent, in more artificialized and dense territories, a clear distinctiveness of water-related concerns in land-use regulations of municipal plans on estuarine areas remains visible. Surprisingly, the results bring to the fore fragilities of land-use regulations on upstream areas worthy of attention in future studies. The methodology used for content analysis disclosed a valuable path for future research as it is easily expandable to take into consideration different land-uses or to be applied to different regions, to further refine if the distinctive features are explicitly related with estuarine areas or with other types of water problems. Highlights: Estuaries are vulnerable to land uses and require land-use control rules. Studies on municipal land-use regulations nearby estuarine locations are scarce. A methodology is designed to assess municipal plans' regulations nearby estuaries. Land-use regulations are more sensitive to water in estuarine in comparison with upstream areas.